The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1128/aac.01596-17
|View full text |Cite
|
Sign up to set email alerts
|

The Alternative Sigma Factors SigE and SigB Are Involved in Tolerance and Persistence to Antitubercular Drugs

Abstract: The emergence and spread of drug-resistant Mycobacterium tuberculosis strains possibly threaten our ability to treat this disease in the future. Even though two new antitubercular drugs have recently been introduced, there is still the need to design new molecules whose mechanisms of action could reduce the length of treatment. We show that two alternative sigma factors of M. tuberculosis (SigE and SigB) have a major role in determining the level of basal resistance to several drugs and the amount of persister… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 31 publications
3
39
0
Order By: Relevance
“…This reduction suggests that sigE is required for tolerance of certain drugs. Indeed, this recapitulates the growth defects observed in a ∆sigE mutant when exposed to various drugs [47]. sigE is an alternative sigma factor that is thought to play a regulatory role in response to various stresses.…”
Section: Application To Datasets With Multiple Conditionssupporting
confidence: 65%
“…This reduction suggests that sigE is required for tolerance of certain drugs. Indeed, this recapitulates the growth defects observed in a ∆sigE mutant when exposed to various drugs [47]. sigE is an alternative sigma factor that is thought to play a regulatory role in response to various stresses.…”
Section: Application To Datasets With Multiple Conditionssupporting
confidence: 65%
“…One example is the association of stochastic variation in katG expression to INH‐tolerance in single mycobacterial cells (Wakamoto et al ., ). Previous studies have shown that mycobacterial σ B is important for stress responses, including cell envelope stress and hypoxia (Fontan et al ., ) and for tolerance to several drugs (Pisu et al ., ; Yang et al ., ). These studies have been performed at the population level.…”
Section: Discussionmentioning
confidence: 97%
“…Deletion of sigB gene did not change the MIC of mycobacteria to INH (Yang et al ., ), but we showed that it decreased the fraction of survivors to INH treatment both under optimal growth conditions and in the starvation model (Fig. ) (Pisu et al ., ), which suggests that σ B may promote Msm tolerance to INH. By using a fluorescent reporter, we demonstrated that the increased expression of σ B positively correlates with INH tolerance, as measured by CFU recovery during INH treatment.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In 2017, we showed that a M. tuberculosis sigE mutant was more susceptible than its parental strain to several drugs, including INH, rifampin, streptomycin, gentamycin, vancomycin, and ethambutol, whereas a sigB mutant was more sensitive only to INH and ethambutol which both target mycolic acids biosynthesis ( Pisu et al, 2017 ). Moreover, we showed that persisters able to escape INH and streptomycin killing occurred less frequently in both mutants compared to the wild type, while those escaping killing by vancomycin appeared less frequently than in the wild type only in the sigE mutant.…”
Section: Role Of Sigma Factors In Tolerance and Persistencementioning
confidence: 99%